QUALITY OF LIFE IN OSTEOPOROSIS - Deniz Adıgüzel,; O. Hakan Gündüz,; Hatice Bodur,; Metin Yücel, (Archives of Rheumatology, 2000)
Osteoporosis is a disease characterized by low bone mass and micro-architectural deterioration of bone tissue with increased fracture risk. It effects large numbers of individuals worldwide, especially the postmenopausal women. Pain, limitation of motion, and vertebral or non-vertebral fractures from osteoporosis makes daily life difficult. Due to pain, limitation of motion, and deformities patients have difficulty in being satisfied with their roles, and meeting their expectations in social relations. In this study we aimed at evaluating the effects of osteoporosis on the quality of life. One hundred thirty postmenopausal women were included to the study. To exclude other diseases, which may have an effect on bone mineral density (BMD), routine biochemical, hematological, and when necessary, hormonal tests were performed. Patients with abnormal results were excluded. According to BMD measurements and World Health Organization criteria, 33 women were normal (mean age 49,18±6,01; mean duration of menopause 3,42±3,99), 51 were osteopenic (mean age 54,03±7,81; mean duration of menopause 7,22±0,95), and 46 were osteoporotic (mean age 62,39±8,15; mean duration of menopause 13,77±8,17). Osteoporotic patients were further grouped according to presence of decrease in body height and history of non-vertebral fractures. Nottingham Health Profile (NHP) quality of life measurement scale was applied to each individual, and 6 scores (pain, physical activity, energy level, sleep, social isolation and emotional reaction) were evaluated. All groups of postmenopausal patients, including the normal BMD group revealed interestingly higher scores in NHP scores. That is, Ôquality of life' was lower in all postmenopausal patients. BMD was negatively correlated with the NHP scores; that is, quality of life was correlated with BMD results. Among the subscores, pain and physical activity scores were particularly correlated with BMD. Normal BMD group had lowest scores in general, except the emotional reaction score. In our study we frequently encountered extreme scores on both lower and higher sides in NHP, and we think that NHP was affected by the characteristics of the study group to a large extent. Therefore in future studies of quality of life measurements in osteoporosis, we think that, selection of a scale that is prepared for Ôosteoporosis' itself, would be more suitable. In spite of all these, NHP may be reliably used in postmenopausal osteoporosis, since it is easy to apply, and also it includes sections that effectively evaluate the clinical consequences like pain, limitation of physical activity together with emotional effects of the disease.